OP0223 Significance of IGG Phosphatidylserine-Dependent Antiprothrombin Antibody Testing for the Diagnosis of Antiphospholipid Syndrome: Results from the Initial and Validation International Multi-Centre Studies. (9th June 2015) - Amengual, O.; Forastiero, R.; Sugiura-Ogasawara, M.; Otomo, K.; Kenji, O.; Favas, C.; Delgado Alves, J.; Žigon, P.; Ambrožič, A.; Tomšič, M.; Ruiz Arruza, I.; Ruiz Irastorza, G.; et al.
Abstract : Background: Phosphatidylserine-dependent antiprothrombin antibodies (aPS/PT) are strongly correlated with lupus anticoagulant. A Task Force of scientists at the International Congress on Antiphospholipid Antibodies (APLA 2010) accepted that aPS/PT would potentially contribute for a better identification of antiphospholipid syndrome (APS). Accordingly, we carried out an Initial and a Validation retrospective, cross-sectional multi-centre study on aPS/PT. Objectives: To ascertain the value of aPS/PT for APS diagnosis. Methods: We conducted an initial study involving 8 centres from 7 countries.Demographics and clinical/laboratory data were retrospectively collected.A sample from the subjects was prepared at each institution.Specimens were blinded and determination of IgG aPS/PT performed at Inova Diagnostics, Inc.USA (Inova) using ELISA kits from two manufacturers:Medical and Biological Laboratories Co Ltd, Japan (MBL) and Inova.After completing the initial study, a Validation study with a new sample of subjects (5 different centres from 5 countries) was carried out using the same methodology. Results: The Initial study comprised 247 subjects.Statistically significant correlation in the IgG aPS/PT values was obtained with both ELISA kits (r=0.827, p<0.001). amples with concordant IgG aPS/PT results in both ELISAs (n=204) were subsequently analyzed (99 APS, 58 non-APS and 47 healthy). IgG aPS/PT was more prevalent in APS patients (51%) than in those without (9%), OR: 10.8 [95%CI 4-29], p<0.0001. Sensitivity, specificity, positive (LR+) and negative (LR-) likelihood ratio of IgG aPS/PT for APS diagnosis were 51%, 94%, 8.9 and 0.5 respectively.The diagnostic accuracy of IgG aPS/PT for APS diagnosis was assessed by ROC curves showing AUC values of 0.782 and 0.777 for MBL and Inova assays, respectively. In the Validation study (n=214) a statistically significant correlation was found in the IgG aPS/PT titers with both ELISAs (r=0.827, p<0.001). IgG aPS/PT concordant samples were analyzed (n=182;76 APS, 57 non-APS and 49 healthy). IgG aPS/PT was more frequent in APS patients (47%) than in those without (12%), OR: 6.4 [95%CI 2.6-16], p<0.0001. Sensitivity, specificity, LR+ and LR- for APS diagnosis were 47%, 93%, 7.2 and 0.6, respectively.AUC values were 0.757 and 0.759 for MBL and Inova assays, respectively. Conclusions: The performance of IgG aPS/PT using Inova and MBL ELISA kits is reliable. IgG aPS/PT detection is an easily performed laboratory parameter that may help in the diagnosis of APS. Acknowledgements: The authors want to acknowledge the contributions of the late Prof. Silvia Pierangeli, University of Texas Medical Branch, Galveston, TX, USA Disclosure of Interest: O. Amengual: None declared, R. Forastiero: None declared, M. Sugiura-Ogasawara: None declared, K. Otomo: None declared, O. Kenji: None declared, C. Favas: None declared, J. Delgado Alves: None declared, P. Žigon: None declared, A. Ambrožič: None declared, M. Tomšič: None declared, I. Ruiz Arruza: None declared, G. Ruiz Irastorza: None declared, M. Bertolaccini: None declared, G. Norman Employee of: Inova Diagnostics, Inc, San Diego, CA USA, Z. Shums: None declared, A. Jiro Employee of: Medical and Biological Laboratories, Co. Ltd, A. Murashima: None declared, A. Tebo: None declared, M. Gerosa: None declared, P. Meroni: None declared, I. Rodriguez-Pintό: None declared, R. Cervera: None declared, J. Swadzba: None declared, J. Musial: None declared, T. Atsumi Grant/research support from: Chugai Pharmaceutical Co., Ltd., Eisai Co., Ltd., Bristol-Myers Squibb Co., Astellas Pharma Inc., Daiichi Sankyo Co., Ltd. and Mitsubishi Tanabe Pharma Co., Speakers bureau: Astellas Pharma Inc. and Mitsubishi Tanabe Pharma Co.